A pilot study exploring quality of life experienced by patients undergoing negative‐pressure wound therapy as part of their wound care treatment compared to patients receiving standard wound care. Issue 4 (24th October 2012) - Ousey, Karen J; Milne, Jeanette; Cook, Leanne; Stephenson, John; Gillibrand, Warren
<x xml:space="preserve">Abstract</x> The use of negative pressure wound therapy (NPWT) has been widely documented as a technique to help heal complex wounds. This article presents the findings of a preliminary study which aimed to explore quality of life (QoL) experienced by patients undergoing NPWT as part of their wound care treatment in comparison to that of patients with a wound using traditional (standard) wound care therapies. A quasi‐experimental study was undertaken, with patients treated in wound care/vascular clinics with chronic/acute wounds. QoL impact was measured using the Cardiff Wound Impact Schedule and administered post‐consent at timed intervals. Our results identified that there were no real differences in QoL scores recorded by patients over the 12‐week period. Although there was no overall interaction between the therapies used for wound healing, NPWT did have an effect on social life: during the first 2 weeks of the application of therapy, patients in the NPWT group reported an increase in the social life domain. The authors conclude that true QoL can only be elicited if an accurate baseline is established or if data is collected over a long enough period to allow comparison of scores over time.